Answer:
To do this, you need to multiply out the expressions. This is a bit tedious, but remember like FOIL for binomials, for these trinomials you must multiply each term. If you need a step-by-step, I'd be happy to provide it. Let me know.
Once you have simplified the expression, you get
-x-9/2x-4
But, the problem stipulates that a must equal 1. We can equivalently factor out the negative sign and put it on the denominator with no change to write
x+9/-(2x-4) = x+9/-2x+4
So, seeing where each coefficient corresponds between the two expressions, you get a = 1, b = 9, c = –2, and d = 4.
Answer:
3. 28pm
Step-by-step explanation:
11 43
+3 45
15 28
15.28-12
=3.28
Answer:
1 out of 3
Step-by-step explanation:
Answer:
1. To eliminate x-term, multiply the second by -2
2. To eliminate y-term, multiply the second by 3
Step-by-step explanation:
4x - 9y = 7 (1)
-2x + 3y = 4 (2)
1. To eliminate x-term, multiply the second by -2
-2x + 3y = 4 (2) × 2
-4x + 6y = 8 (3)
4x - 9y = 7 (1)
Add (3) and (1)
6y - 9y = 8 + 7
-3y = 15
y = 15/-3
y = -5
4x - 9y = 7 (1)
4x - 9(-5) = 7
4x + 45 = 7
4x = 7 - 45
4x = -38
x = -38/4
x = -9.5
4x - 9y = 7 (1)
-2x + 3y = 4 (2)
2. To eliminate y-term, multiply the second by 3
-2x + 3y = 4 (2) × 3
-6x + 9y = 12 (3)
4x - 9y = 7 (1)
-6x + 4x = 12 + 7
-2x = 19
x = 19/-2
x = -9.5
4x - 9y = 7 (1)
4(-9.5) - 9y = 7
-38 - 9y = 7
-38 - 7 = 9y
-45 = 9y
y = -45/9
y = -5
<span>I think any of those estimates are correct since we don't have a value for the width and length so acquiring the actual measurement its impossible. All possible answers are correctly written in square units.</span>